Double cantilever-beam test comparisons of Mode I fracture toughness of adherends bonded using DP8010 and DP8005 acrylic-based adhesives. (April 2018) - Kim, Hyun-Bum; Naito, Kimiyoshi; Oguma, Hiroyuki
Abstract: The aim of this study is to not only measure the fracture toughness ( G IC ) of adherends bonded with a DP8010 acrylic-based adhesive using double cantilever beam (DCB) specimens under Mode I loading, but also to compare them with those bonded with DP8005. Aluminum alloy (5052-H34), glass fiber-reinforced polypropylene matrix composite (GF/PP), and carbon fiber-reinforced epoxy matrix composite (CF/EP) are used as adherends. Tensile tests of the adhesive bulk specimens are performed to measure the mechanical properties. R −curves measured from DP8010 and DP8005 are evaluated by relating them with failure modes observed from the fracture surfaces. Traction−normal separation relationships are considered to compare the fracture behaviors between DP8010 and DP8005. The experimental results show that the modulus of toughness ( u r ) for the adhesive bulk specimen of DP8010 exhibits similar values with that of DP8005. To maximize the values of G IC using acrylic-based adhesives, the following conditions need to be considered: ① strong bonding between adhesive and adherend, ② defect-free adherends, and ③ high ductile behavior of the adhesive bulk specimen.